Existence and Uniqueness of Solutions for a Second-Order Delay Differential Equation Boundary Value Problem on the Half-Line. (10th September 2008) - Wei, Yuming
Abstract : This paper is concerned with the existence and uniqueness of solutions for the second-order nonlinear delay differential equations. By the use of the Schauder fixed point theorem, the existence of the solutions on the half-line is derived. Via the Banach contraction principle, another result concerning the existence and uniqueness of solutions on the half-line is established. The main results in this paper extend some of the existing literatures.